How does market competition affect firm innovation incentives in emerging countries? Evidence from Chile and Colombia - José Miguel Benavente H.; Pluvia Zuniga (Inter-American Development Bank (IDB), 2022)
The effect of market competition on firm innovation remains controversial, especially in the context of developing countries. This paper presents new empirical evidence about the causal impact of competition on firm innovation for Chilean and Colombian manufacturing firms. Using instrumental-variable estimation, our results show that market competition increases firm propensity to invest in innovation, but this relationship manifests differently in the two countries. While this relationship is linear in Chilean firms, an inversed-U shaped relation prevails in Colombian firms. In both countries, however, innovation incentives are mostly concentrated in the medium range of the firm productivity distribution. These findings are robust to including past innovation engagement, import competition, and business dynamics. In addition, first- stage estimations show that competition law interventions improved market competition in sanctioned sectors while business entry reforms significantly leveraged competition across industries. These findings stress the importance of pro-competition regulations and competition policy, not only to benefit consumers' welfare but also to support firm innovation.
Keywords: O32; D41; O47; D24; 330; competition; innovation; productivity; Chilean firms; Colombian firms